The impact of patients controlled analgesia undergoing orthopedic surgery - Dias,Aluane Silva (2016)
ABSTRACT INTRODUCTION: The currently common musculoskeletal disorders have been increasingly treated surgically, and the pain can be a limiting factor in postoperative rehabilitation. RATIONALE: Patient controlled analgesia (PCA) controls pain, but its adverse effects can interfere with rehabilitation and in the patient discharge process. This study becomes important, since there are few studies evaluating this correlation. OBJECTIVES: To compare the outcomes of patients who used and did not use patient controlled analgesia in postoperative orthopedic surgery with respect to pain, unscheduled need for O2 (oxygen), and time of immobility and in-hospital length of stay. METHODS: This is an observational, prospective study conducted at Hospital Abreu Sodré from May to August 2012. The data was daily obtained through assessments and interviews of patients undergoing total hip arthroplasty (THA) and total knee arthroplasty (TKA), thoracolumbar spine arthrodesis (long PVA), cervical spine arthrodesis (cervical AVA) and lumbar spine arthrodesis (lumbar PVA). RESULTS: The study showed some differences between groups, namely: the painful level was higher in the group undergoing lumbar PVA without PCA compared with the group with PCA (p = 0.03) and in the group of long PVA without PCA in the early postoperative period. This latter group used O2 for a longer time (p = 0.09). CONCLUSION: In this study, PCA was useful for analgesia in patients undergoing lumbar PVA and probably would have influenced the usage time of O2 in the group of long PVA in face of a larger sample. The use of PCA did not influence the time of leaving the bed and the in-hospital length of stay for the patients studied.